Government debt-economic growth nexus in Asean-4 countries - Hajian, Hoda; Kaliappan, Shivee Ranjanee; Mohamed, Azali (Universitas Airlangga, 2022)
Given a background of controversial political and theoretical academic debate and diverse empirical result, as Checherita and Rother (2010) concluded government debt and economic growth relationship is a country specific issue. This paper aims to investigate the causal and dynamic effect of government debt on output growth in the context of developing economies with generally medium debt regime in ASEAN-4 countries. Namely, Indonesia, Malaysia, the Philippines and Thailand during 1985 to 2019 years. A robust multi-variable vector autoregressive (VAR) model at level is employed to capture the long run relations, and causality is addressed using Toda-Yamamoto (1995) approach. As a by-product of the analysis the effect of government debt on two essential factors of sustainable GDP growth, namely, private capital formation and human capital is examined. The findings of this paper which contrast with the general negative effect found in some empirical studies for developing countries, shows debt does not cause output growth in Indonesia, Malaysia and Thailand but the reverse is true. GDP response to debt shock is negative, positive and positive, respectively yet statistically insignificant. In other hand, in the Philippines the result shows the economy is debt-driven as debt positively cause GDP without improving private investment or human capital. Overall, the findings support well debt management. Given current debt regime, improvements on tax collection and government fund allocation in terms of priorities and efficiencies must be continued.